The Economic Cost of the Israeli Occupation for the Palestinian People: The Unrealized Oil and Natural Gas Potential - United Nations Conference on Trade; Development (United Nations, 2019)
This study identifies and assesses existing and potential Palestinian oil and natural gas reserves that could be exploited for the benefit of the Palestinian people that Israel is either preventing them from exploiting or is exploiting itself without due regard to international law.